Excited state processes in linear conjugated systems - Šebelík, Václav (Jihočeská univerzita, 2020)
The main topics of this thesis are the excited states of carotenoids in solvents and in light-harvesting antennas. The first two chapters provide an introduction into the topic, while the later ones are the research chapters, based on published papers. In the research section, the different methods of ultrafast spectroscopy were used. Transient absorption spectroscopy, two-photon excitation, and pump-dump-probe experiments were used to explore the so-called dark states of carotenoids in solvents. The femtosecond dynamics of long polyenes was also studied by the transient absorption spectroscopy. In addition to the exploration of the nature of carotenoids and polyenes in solvents, the energy transfer in the CAC antenna of Rhodomonas salina was studied by transient absorption spectroscopy.
Excited state processes in linear conjugated systems
Keywords: carotenoids; transient absorption spectroscopy; two-photon excitation; pump-dump-probe; polyenes; dark states; carotenoids; transient absorption spectroscopy; two-photon excitation; pump-dump-probe; polyenes; dark states; light-harvesting antenna